EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIRS SHARE (TPS) MENGGUNAKAN MEDIA FLASH PLAYER PADA MATERI FAKTORISASI SUKU ALJABAR - Sukirno Sukirno (MEDIA DIDAKTIKA, 2017)
Education as an integral part of community life in the global era should be able to provide and facilitate the growth of intelectual skills, social and personal. But apparently there were still many problems that arise in the school, including the following: the method used in mathematic instruction was lectures, discussion, and discussion, it had never implement cooperative learning model Think Pairs Share, and had never been implementing instructional media flash player. From the results of learning activities that had been performed for two cycles, and based the entire discussion and analysis had been done can be summarized as follows: (1) The type of cooperative learning model TPS (think pair share) with flash media player had a positive impact in improving student achievement marked by increased mastery learning students in each cycle, that cycle I = 58.3% and cycle II = 88.9 %; (2) The implementation of cooperative learning model TPS (think pair share) with flash media player had a positive influence. Keywords: , ,